Quorum Sensing Signaling in Bacteria - from Mechanism to Future Prospects: A Terse Literature Review - Ogueke, Chika Crescence; Agunwah, Ijeoma Maureen; Ofoedu, Chigozie Emmanuel; Okpala, Charles Odilichukwu R; Korzeniowska, Małgorzata (Asian Journal of Biological and Life Sciences)
Quorum sensing is when a sufficient population of micro-organisms, such as bacteria, situated in a given environment can trigger a system of cell-cell communication in these micro-organisms. Researchers, increasingly, have shown that bacteria are unable to thrive independently as solitary cells, but as colonial organisms, communicating intercellularly, and enhancing their capacity to adapt to changing environmental conditions. To a great extent, researchers today have come to terms with the intricacies surrounding bacterial conversations, and responses/signals. Herein, the quorum sensing and its signaling in bacteria, from briefs about the mechanism, its discovery, and involved molecules, to its applications/uses has been tersely reviewed. Understanding bacteria quorum sensing mechanisms/processes can be very challenging. Several strategies employed to disrupt quorum sensing in bacteria have involved receptor inactivation, signaled synthesis inhibition including its degradation, blocking of quorum sensing using antibodies, as well as the combination of antibiotics and anti-quorum sensing agents. The future use of quorum sensing is hopeful, given the emerging applications like its use in biofouling reduction, biofuel production, biodegradation as well as winemaking.
Keywords: Auto inducer; Bacteria; Bio-preservatives; Inhibitors; Pathogens; Quorum sensing signals